Studi habitat Meranti Merah di Desa Oki Lama Kecamatan Namrole Kabupaten Buru Selatan - Solissa, Renaldo; Siahaya, Ludia; HAponno, Hendrik SES (MAKILA, 2023)
This study aims to determine the Red Meranti species' growing place (habitat) (Shorea selanica B.L) in Oki Lama Village, Namrole District, South Buru Regency. This research was carried out by sampling method; 100 m x 100m observation blocks were taken, and vegetation data were taken utilizing pathways with a systematic sampling inventory method. Vegetation analysis to determine relative density dominance, relative dominance, frequency, relative frequency, and essential value index. The types of trees found in the research location of red meranti trees, pulai, resin, Langsatt, and durian. On line 2 can be seen the largest INP value in red meranti trees, amounting to 249.4641. The habitat conditions of the Red Meranti tree (Shorea selenic) found during the study were all trees growing in places with kambisol soil types overgrown with shrubs with hilly and mountainous conditions at an altitude of 134 m above sea level. At the research site, the air temperature of all trees was 29 ° C and 30 ° C, as well as soil pH and soil moisture, where the pH was 6.2 and 7.06, and light intensity ranged from 212-583 lux.